GAUGING GREENHOUSE EMISSION THROUGH CBA, TRADE, FDI, AND POPULATION GROWTH - Nisa', Milhatun (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: Greenhouse gas emissions have a massive effect on the thinning of the earth's ozone layer, nowadays the industry is obligated to be as responsible for the process and output as possible in order to reduce carbon dioxide emissions (CO2). This study examines the implications of consumption-based accounting, trade, and foreign direct investment on greenhouse gas emissions from the least five emitters of different fuel types, according to the World Research Institute Indonesia, which are Japan, Brazil, Indonesia, Iran, and Canada from 2000 until 2020. Methods: The study employs a panel data regression using Random Effect Model-Hausman Test. Results: The findings show that foreign direct investment has a strong negative association with lowering greenhouse gas emissions. The greater the investment, the cleaner the air and atmosphere. Trade has a negative correlation with greenhouse gas emissions, this reflects increasing environmental consciousness among producers and/or increasing pressure for environmentally friendly operations from oversea. Since natural assets could convey their full economic potential on a sustainable ground. The population had a role in lowering carbon emissions as well. The results of the consumption-based emission regression show a significant positive relationship, which can clearly exacerbate climate change conditions. It is not astounding, given that CBA accounts for emissions throughout a product's or service's complete lifecycle. Conclusion and suggestion: This study advances the grasp of greenhouse gas emissions and the factors that influence others in the five lowest emitters. It is the first study towards using greenhouse gas emission data as the dependent variable, rather than consumption-based accounting data, which has been used in most previous studies.